Revisión crítica de herramientas para monitoreo y gestión en transformadores de distribución ante la integración de recursos de energía distribuida - Cardozo-Cabal, María Carolina; Castro Aranda, Ferley; Gómez Luna, Eduardo (Ingeniería, 2022)
This article presents the critical analysis on the current state of the tools for monitoring and management in distribution transformers in the face of the integration of distributed energy resources, a current topic and of great relevance for the Colombian electricity sector given the high integration of Distributed energy resources (DER), which makes it necessary to provide the productive sector with this work which summarizes the main tools used worldwide to monitor and supervise the distribution transformers that leave the system without any supervision.